Effect of Tricuspid Regurgitation and the Right Heart on Survival After Transcatheter Aortic Valve Replacement. (April 2015) - Lindman, Brian R.; Maniar, Hersh S.; Jaber, Wael A.; Lerakis, Stamatios; Mack, Michael J.; Suri, Rakesh M.; Thourani, Vinod H.; Babaliaros, Vasilis; Kereiakes, Dean J.; Whisenant, Brian; Miller, D. Craig; Tuzcu, E. Murat; et al.
<x xml:space="preserve">Abstract</x> Background— Tricuspid regurgitation (TR) and right ventricular (RV) dysfunction adversely affect outcomes in patients with heart failure or mitral valve disease, but their impact on outcomes in patients with aortic stenosis treated with transcatheter aortic valve replacement has not been well characterized. Methods and Results— Among 542 patients with symptomatic aortic stenosis treated in the Placement of Aortic Transcatheter Valves (PARTNER) II trial (inoperable cohort) with a Sapien or Sapien XT valve via a transfemoral approach, baseline TR severity, right atrial and RV size and RV function were evaluated by echocardiography according to established guidelines. One-year mortality was 16.9%, 17.2%, 32.6%, and 61.1% for patients with no/trace (n=167), mild (n=205), moderate (n=117), and severe (n=18) TR, respectively (P<0.001). Increasing severity of RV dysfunction as well as right atrial and RV enlargement were also associated with increased mortality (P<0.001). After multivariable adjustment, severe TR (hazard ratio, 3.20; 95% confidence interval, 1.50–6.82; P=0.003) and moderate TR (hazard ratio, 1.60; 95% confidence interval, 1.02–2.52; P=0.042) remained associated with increased mortality as did right atrial and RV enlargement, but not RV dysfunction. There was an interaction between TR and mitral regurgitation severity (P=0.04); the increased hazard of death associated with moderate/severe TR only occurred in those with no/trace/mild mitral regurgitation. Conclusions— In inoperable patients treated with transcatheter aortic valve replacement, moderate or severe TR and right heart enlargement are independently associated with increased 1-year mortality; however, the association between moderate or severe TR and an increased hazard of death was only found in those with minimal mitral regurgitation at baseline. These findings may improve our assessment of anticipated benefit from transcatheter aortic valve replacement and support the need for future studies on TR and the right heart, including whether concomitant treatment of TR in operable but high-risk patients with aortic stenosis is warranted. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01314313.